Best practice guide on the control of lead in drinking water - Hayes, Colin (Metals and related substances in drinking water series., 2010)
The Best Practice Guide on the Control of Lead in Drinking Water brings together, for the first time, all of the regulatory, health, monitoring, risk assessment, operational and technological issues relevant to the control of lead in drinking water.